Relationship Between Soil Density And Soil Organic Carbon Stock In Tembawang Agroforestry Area Of Semayang Village Sanggau Regency - Wahyudi, Miki; Rafdinal; Turnip, Masnur (Universitas Sam Ratulangi, 2026)
Tembawang agroforestry is composed of tree vegetation that stores abundant carbon reserves both on the surface and in the soil. Soil organic carbon plays a role in increasing soil fertility so that plant productivity and the sustainability of plant life can increase. The purpose of this study was to determine organic carbon content, and organic carbon reserve and their relationship in the Tembawang Agroforestry of Sanggau Regency. This research was conducted from August 2024 to December 2024. Determination of sampling locations using purposive sampling method. Sampling was done at 5 points in each location. Determination of organic carbon content using the Walkey and Black method. Data were analyzed using the SPSS 30 program. The results of this study show that the soil density is 0,6615 g/cm3 to 0,7795 g/cm3. The highest organic carbon content was 7.08% then decreased to 2.89%. Soil organic carbon reserves were 2311,38 ton/ha to 6735,60 ton/ha. Soil density had a week negative correlation with organic carbon content (r = -0,240 < 0,05) and a moderate positive correlation with organic carbon stocks (r = 0,546 < 0,01). Organic carbon content had a strong negative correlation with organic carbon reserves (r = -0,681 < 0,01).